Implementasi job order costing pada Penjahit Citra di Sumba Timur - Melanium Gloria Nicolas; Norman Duma Sitinjak (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2023)
Micro, Small and Medium Enterprises is a general term in the economic world of productive businesses owned by individuals and business entities that have met the criteria as micro enterprises. One of the businesses that fall into the criteria of a small business is a sewing business. The formulation of the problem from this research is "How is the system for calculating the cost of goods based on Job Order Costing in the "Image Tailor" business?". The purpose of this study is to find out the system of calculating the cost of goods based on Job Order Costing in the "Image Tailor" business. The data collection technique used a direct question and answer technique with the owner of the "Image Tailor" business in East Sumba and quoted data from the "Image Tailor" business. Cost of Orders or Job Order Costing is a method of calculating production costs in accordance with orders from consumers. In the calculation according to the Job Order Costing method, tailor overhead costs are calculated based on a proportion of 70% obtained from the total production of official uniforms divided by the total production in January 2022.